2018
DOI: 10.1111/geb.12725
|View full text |Cite
|
Sign up to set email alerts
|

From tropical shelters to temperate defaunation: The relationship between agricultural transition stage and the distribution of threatened mammals

Abstract: Aim: Agriculture is a key threat to biodiversity; however, its relationship with biodiversity patterns is understudied. Here, we evaluate how the extent, intensity and history of croplands relate to the global distribution of threatened mammals. We propose two hypotheses to explain these relationships: shelter, which predicts that threatened species concentrate in areas with low human land use; and threat, according to which threatened species should concentrate in areas of high human land use.Location: Global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…On the other hand, areas modified at a more constant pace throughout history (e.g. Europe or India) may have more resilient species, as these areas are more likely to have suffered more severe extinction filters in the past (Newbold et al 2018, Polaina et al 2018.…”
Section: Globalmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, areas modified at a more constant pace throughout history (e.g. Europe or India) may have more resilient species, as these areas are more likely to have suffered more severe extinction filters in the past (Newbold et al 2018, Polaina et al 2018.…”
Section: Globalmentioning
confidence: 99%
“…These studies have often used broad study units such as ecoregions or countries, and have linked the occurrence of threatened species with human pressures, measured in terms of land use or human population density (Lenzen et al 2009, Pekin and Pijanowski 2012, Brum et al 2013) and with different socioeconomic profiles (Polaina et al 2015). Polaina et al (2018) analyzed threatened species richness at a finer resolution (1 × 1° grid cells) and showed that the relationship between this biodiversity metric and land-usechange derived impacts varied across regions, likely reflecting different stages of human development and appropriation of land. In some areas, threatened species were more abundant in more impacted areas, whereas in others threatened species remained in less impacted zones.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, I argue that there is a need for a standardized monitoring of endangered mammals species data, for gathering of intensive data and evidences on the changes in forested landscape, and of detailed data on negative impacts of any forest activity on forests like clear-cutting, selective logging (selective tree cutting), mechanization use (for tree removal), of forest activity noise, and on the stage of agriculture development. Ester et al (2018) found that different stages of agriculture landscape (high intensified, low intensified agriculture) determined the distribution of terrestrial mammal species. Strindberg et al (2018) measured the canopy height (Gorilla beringei species preferred high trees between 25 m to 35 m), to distinguish between selective logging (high trees) and swap forests (shorter trees) and found that tropical forests were degraded, when selective logging was applied.…”
Section: Data Differencesmentioning
confidence: 99%
“…Threatened terrestrial mammal species can possibly occupy frontier landscape for refuge (shelter). (Estavillo et al, 2013;Fernández et al, 2003;Kanagaraj et al, 2011;Rogers & Gorman, 1995;Fernandez et al, 2006;Nüchel et al, 2018;Ester et al, 2018) packages of 'bbmle', 'biodiversityR', 'biomod2', 'brglm', 'DAAG', 'foreign', 'glmmboot', 'verification'. There were thirty-five candidate models fitted (one GLM model for each species).…”
Section: Endangered Species Modelsmentioning
confidence: 99%
See 1 more Smart Citation